2022
DOI: 10.1007/s12029-022-00855-7
|View full text |Cite|
|
Sign up to set email alerts
|

The “Weekday Effect”—Does It Impact Esophageal Cancer Surgery Outcomes?

Abstract: Background: Increased 30-day mortality rates have been reported in patients undergoing elective surgery later compared with earlier in the week. However, these reports have been con icting for esophageal surgery. We conducted a study to assess the differences in outcomes of patients undergoing surgery for esophageal cancer earlier in the week (Tuesday) versus later (Friday).Methods: This retrospective analysis of a prospectively maintained database included patients with esophageal cancer who underwent esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This observation hints at a potential systematic phenomenon tied to operational practices within healthcare settings. However, this ‘weekday effect’ hypothesis is not unanimously supported as other studies found no significant impact of the day of the week on the outcomes of elective oncological resections 6 8 . This discrepancy in findings could be attributed to variations in healthcare systems between countries, differences in study design, or disparities in the clinical conditions being studied.…”
Section: Introductionmentioning
confidence: 90%
“…This observation hints at a potential systematic phenomenon tied to operational practices within healthcare settings. However, this ‘weekday effect’ hypothesis is not unanimously supported as other studies found no significant impact of the day of the week on the outcomes of elective oncological resections 6 8 . This discrepancy in findings could be attributed to variations in healthcare systems between countries, differences in study design, or disparities in the clinical conditions being studied.…”
Section: Introductionmentioning
confidence: 90%